Effect of dietary incorporation of fish/prawn meal on performance of Catla catla (Hamilton) during nursery phase - Das, Pratap Chandra; Kamble, Suhas Prakash; Parida, Kartik Chandra; Mohanta, Kedar Nath (Indian Journal of Fisheries, 2017)
Nursery evaluation of catla spawn was carried out by feeding three iso-nitrogenous diets (35% protein in raw and cooked form) for a period of 30 days. The three test diets (treatments) in raw form were: T1 - groundnut oil cake (GOC) + rice bran (RB) + vitamin-mineral (V-M) premix; T2 - GOC+RB+fish meal (FM) + V-M premix, T3 - GOC+RB+prawn meal (PM)+V-M premix. The diet groups GT1, GT2 and GT3 respectively were same feed combinations in cooked form. Incorporation of prawn meal as animal protein source led to significantly higher final weight, final length, % weight gain, specific growth rate (SGR) and protein efficiency ratio (PER) compared to diet with and without fish meal incorporation. Whereas, diet containing fish meal improved the fry growth and survival rate only when it was cooked. Cooked diet either with fish or prawn meal incorporation led to better fry growth over the respective non-cooked diets, revealing the advantage of cooking process for better nourishment in catla fry during nursery phase.